2012
DOI: 10.1093/toxsci/kfs214
|View full text |Cite
|
Sign up to set email alerts
|

Toxicogenomic Profiles in Relation to Maternal Immunotoxic Exposure and Immune Functionality in Newborns

Abstract: A crucial period for the development of the immune system occurs in utero. This results in a high fetal vulnerability to immunotoxic exposure, and indeed, immunotoxic effects have been reported, demonstrating negative effects on immune-related health outcomes and immune functionality. Within the NewGeneris cohort BraMat, a subcohort of the Norwegian Mother and Child Cohort Study (MoBa), immunotoxicity was demonstrated for polychlorinated biphenyls and dioxins, showing associations between estimated maternal in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
29
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(31 citation statements)
references
References 38 publications
2
29
0
Order By: Relevance
“…These observations suggest early life AHR activation influences CD8 + T cell function later in life without causing overt immunotoxicity. Consistent with these potential mechanisms discussed here, recent human transcriptomic data show correlations between fetal exposure to AHR-binding pollutants, including TCDD, and altered expression of genes involved in immune regulation, cell cycle and antigen processing and presentation in cord blood cells (62). …”
Section: Discussionsupporting
confidence: 79%
“…These observations suggest early life AHR activation influences CD8 + T cell function later in life without causing overt immunotoxicity. Consistent with these potential mechanisms discussed here, recent human transcriptomic data show correlations between fetal exposure to AHR-binding pollutants, including TCDD, and altered expression of genes involved in immune regulation, cell cycle and antigen processing and presentation in cord blood cells (62). …”
Section: Discussionsupporting
confidence: 79%
“…The gender‐specific effects observed in this study were confirmed and extended in a second study on cord blood samples from 45 male and 66 female newborns [Hochstenbach et al, ] which made use of transcriptomics as well as multiple additional biomarkers. These biomarkers included (a) DR‐, ER‐ and AR‐CALUX, which reflect exposure to chemicals interacting with the dioxin‐, estrogen‐, and androgen‐receptors, respectively (e.g., polychlorinated dibenzodioxins, dibenzofurans and biphenyls, and endocrine disruptors such as DDT and antiandrogens), (b) haemoglobin adducts of acrylamide and glycidamide, biomarkers of dietary exposure to acrylamide produced during food processing, and (c) micronuclei as a biomarker of cancer risk.…”
Section: Polychlorinated Hydrocarbonssupporting
confidence: 79%
“…For example, Hochstenbach et al [37] established toxicogenomic profiles in relation to maternal immunotoxic exposure and immune functionality in newborns, and Pennings et al [38] found cord blood gene expression profiles supporting that prenatal exposure to perfluoralkyl substances caused depressed immune functionality in early childhood. In vitro assays which evaluate immunosuppression are generally not used to form a basis for risk assessment.…”
Section: The Use Of Immunotoxicity Data In Risk Assessmentmentioning
confidence: 99%